Ownership of Rights to Land Access to Citizen Perspective of Wahbah Az-Zuhaili - Fadilah Anisa Ritonga; Cahaya Permata (Jurnal Hukum dan Kenotariatan, 2023)
Everything that exists in the heavens and the earth including the land in the Islamic view belongs to Allah SWT. But God gives authority to humans to manage and own it. A person's ownership of land gives him the power to interpret it. Ownership in Islam consists of private and public property rights, but neither is absolute. Because, in every property owned by a person there are other people's rights. Thus, one's ownership of land must carry out its social function. However, there are cases of landowners blocking access to and from local residents' houses on the basis of property rights. The purpose of this research is to find out the factors causing the closure of access in and out of the road, how it is regulated in Indonesia and how the concept of ownership of land rights which is access in and out according to Wahbah az-Zuhaili. This type of research is empirical juridical using a case approach (living case approaach) and conceptual approach (conceptual approach). Data were collected by interview, observation and document study methods. Then the data is processed with qualitative methods. The results of this study indicate that the closure of access in and out of the road that occurred in Kampung Bukit Kota Padangsidimpuan violated the concept of ownership in the form of milkiyah rights where the concept of land ownership in Islam has limitations, not all assets can be owned individually (individually), one of which is assets owned by have public utilities including roads. In accordance with the opinion of Wahbah az-Zuhaili, that a person's penance for his property should not cause harm to many people.